ISLAMIC COMMERCIAL BANKS: AN ANALYSIS THE DETERMINANTS OF PROFIT DISTRIBUTION MANAGEMENT - Aprih Santoso; Joko Samboro (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The study examines the effect of Capital Adequacy Ratio (CAR) on Profit Distribution Management (PDM) with Return on Assets (ROA) as a mediating variable in Islamic Commercial Banks (BUS) for the 2010-2020 period. The population includes all BUS in Indonesia registered with the Financial Services Authority (OJK), which successively reports 9 BUS financial statements. The sampling technique used is purposive sampling. The analysis technique used is path analysis. The results showed that CAR had a positive and significant effect on ROA.On the other hand, CAR and ROA positively and significantly impact PDM. Else, ROA can mediate the effect of CAR on PDM. Information and evaluation of the company's financial performance minimize error decisions.